Vietnam-China economic cooperation: An ambivalent engagement - Zaharul Abdullah; Noor Ashikin Said; Mohamad Ikhram Mohamad Ridzuan (Penerbit Universiti Sains Malaysia, 2025)
Southeast Asia holds a significant role in China’s Belt and Road Initiative (BRI), particularly in the 21st Century Maritime Silk Road (MSR). Despite the substantial power asymmetry between Southeast Asian nations and China, their responses to the BRI vary, falling into categories such as “the embracers”, “the cautious collaborators”, and “the sceptics”. Vietnam, specifically, has been categorised as “the sceptic” due to the absence of BRI-labelled projects and limited uptake of BRI loans, despite offering diplomatic support to the initiative and joining the Asian Infrastructure Investment Bank (AIIB) as a founding member. This article contends that such a label fails to capture Vietnam’s overall economic engagement with China, which can be characterised as “ambivalent engagement”. It argues that while Vietnam exhibits passive resistance towards the BRI, it actively engages in trade, investment, project contracting in energy sector, and economic corridor cooperation with China. This characterisation aligns with Vietnam’s established strategy of engaging with China through a combination of “both cooperation and struggle”. These diverse patterns of agency can be understood through the lens of elite legitimation and external alternatives. By doing so, this article seeks to enrich Kuik’s typology on host-country agency within the context of Southeast Asian states’ responses to the BRI and economic collaboration with China, thereby contributing to the literature on the asymmetry-authority framework.